The Relationship Between Army Soldiers' Perceived Stress and Army Life Adjustment: Focusing on the Mediating Effect of Stress Response and the Moderating Effect of Cohesion. Issue 9 (28th May 2020) - Ha, Jung Hee; Jue, Juliet; Jang, Yoojin
Abstract: Introduction: South Korea maintains a mandatory military duty, and high percentage of conscript soldiers have difficulty adjusting to military life. The purpose of this study is to investigate the mediating effect of the stress response on the relationship between soldiers' perceived stress and military life adjustment and to clarify the moderating effect of cohesion on this relationship. Materials and Methods: The study's participants were 285 Korean military soldiers who are obliged to serve in the military and they completed the Perceived Stress Scale, the Stress Response Scale, the Military Life Adjustment, and the Group Cohesion Scale. Analysis methods included descriptive statistics, correlation analysis, path analysis, bootstrapping, collinearity statistic, and hierarchical regression analysis. This research obtained the approval of the institutional review board of the university (HYI-18-229-1). Results: First, a partial mediation effect of the stress response was found in the relationship between soldiers' perceived stress and military life adjustment. That is, a high level of soldiers' perceived stress was related to their military life maladjustment. Moreover, the greater the level of soldiers' perceived stress, the greater the stress response, and, in turn, the greater the military life maladjustment. Second, we found the moderating effect of cohesion in the relationship between stress perception and military life adjustment. Conclusions: The stress perceived by soldiers not only directly affects their military life adjustment but also indirectly affects their adjustment through the stress responses. In addition, soldiers' levels of adjustment to military life change significantly based on cohesion levels only when they perceive less stress.